OPTIONS FOR MAINTENANCE OF THE CURRENT SYSTEMS OF TRACK WITH MECHANIZED COMPLEXES - Blazhko, L. S. (Science and Transport Progress, 2003)
The alternative choice questions are considered for the track maintenance by the machine complexes under the transition the track keeping of MPS RF to new management and control systems providing the maintenance expences reduction. The transition takes place in accordance with the general administration and management reorganization of railway transport.